'Pain Always Asks for a Cause': Nietzsche and Explanation. (12th April 2017) - Bennett, Matthew
Abstract: Those who have emphasised Nietzsche's naturalism have often claimed that he emulates natural scientific methods by offering causal explanations of psychological, social, and moral phenomena. In order to render Nietzsche's method consistent with his methodology, such readers of Nietzsche have also claimed that his objections to the use of causal explanations are based on a limited scepticism concerning the veracity of causal explanations. My contention is that proponents of this reading are wrong about both Nietzsche's methodology and his method. I argue for this by: first, showing that Nietzsche was suspicious of causal explanations not only on sceptical grounds but also for reasons provided by his psychological analysis of our tendency to look for causes; and second, arguing for a non‐causal interpretation of Nietzsche's approach to psychological explanation.